(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article considers valency of somatic phraseological units in the Kazakh language. The examples illustrate verbal valence of somatic phraseological units and also consider somatic phraseology a valence of nouns, adjectives and adverbs. In the given examples bilateral opinion about valency and it’s compatibility in language are compared The article defines that valency of verbal somatic phraseological units is stronger, and somatic phraseological units of nouns, adjectives and adverbs are found only in sentences.